The Gene Hunters: Biotechnology and the Scramble for Seeds - Calestous Juma (Princeton University Press, 2014)
In his analysis of the impacts of Old World animals and plants in the Americas, Crosby described in detail the major ecological oscillations that resulted from the introduction of new life forms. He concluded: 'This wild oscillation of the balance of nature happens again whenever an area previously isolated is opened to the rest of the world. But possibly it will never be repeated in as spectacular a fashion as in the Americas in the first post-Columbian century, not unless there is, one day, an exchange of life forms between planets.'1 These words were written in 1972. A year later, US scientists cloned the gene. Since then, scientists have marshalled enough knowledge to modify existing life forms and create new plants and animals. The world is on the verge of receiving life forms whose economic and ecological implications are likely to rival the effects of the Columbian exchange. Writing almost at the same time, de Janvry pointed out that '[Bliological innovations have relatively little effect on labour and management requirements. They are slightly capital using and moderately yield increasing when used outside of complete packages of techniques.'2 This assertion has neither been supported by the experiences of the Green Revolution nor advances in biotechnology. The potential impacts of advances in biotechnology will not only be irreversible, but they will also introduce major and unpredictable transformations in the global organization and distribution of production which will have far-reaching implications for Africa. This, together with its historical antecedents, is the theme of this book. In the last decade the world has experienced major advances in technological change. The use of micro-electronics or information technology has moved from the consumer sector to the capital goods sector - the very heart of industrial production. Biotechnology, on the other hand, promises to make major inroads into the productive sector. These changes are likely to have profound effects on the world economy and the agricultural sector is likely to experience some of the earliest effects. Countries which rely on the export of high-value agricultural commodities are likely to be affected by these advances. African countries, for example, will be required to make adaptations in their agricultural practices. Their responses will depend largely on their capacity to use some of the modern techniques in biotechnology as well as conserve biological diversity as a basis for renewed agricultural production. In order to understand the advances in biotechnology and their implications, it is necessary to place the developments in a historical perspective